Computed tomography follow-up identifies radically treatable new primaries after resection for lung cancer. (25th October 2019) - Mitchell, Jenny; Benamore, Rachel; Gleeson, Fergus; Belcher, Elizabeth
Abstract: : OBJECTIVES: The optimal imaging programme for the follow-up of patients who have undergone resection of primary lung cancer is yet to be determined. We investigated the incidence and patterns of new and recurrent malignancy after resection for early-stage lung cancer in patients enrolled into a computed tomography (CT) follow-up programme. METHODS: We reviewed the outcomes of consecutive patients who underwent CT follow-up after resection of early-stage primary lung cancer at the Oxford University Hospitals NHS Foundation Trust, between 2013 and 2017. RESULTS: Four hundred and sixty-six consecutive patients underwent resection of primary lung cancer between 1 January 2013 and 31 March 2017. Three hundred and thirty-one patients (71.0%) were enrolled in CT follow-up. The median follow-up was 98 weeks (range 26–262). Sixty patients (18.2%) were diagnosed with programme-detected malignancy. Recurrence was diagnosed in 36 patients (10.9%), new primary lung cancer in 16 patients (4.8%) and non-lung primary tumours in 8 patients (2.4%). A routine CT scan identified the majority of new primary lung cancers (84.2%) and those with disease recurrence (85.7%). The majority of programme-detected malignancies were radically treatable (55%). The median survival of programme-detected cancers was 92.4 versus 23.0 weeks for patients with clinically detected tumours ( P  < 0.0001). Utilizing the CT scout image as a surrogate for chest X-ray, the sensitivity of this modality was 16.95% (8.44–28.97%) and specificity was 89.83% (79.17–96.18%). Negative likelihood ratio was 0.92 (0.8–1.07). CONCLUSIONS: CT follow-up of surgically treated primary lung cancer patients identifies malignancy at a stage where radical treatment is possible in the majority of patients. Chest X-ray follow-up may not be of benefit following lung cancer resection.